2012
DOI: 10.1124/mol.112.080911
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multiple Histamine H4 Receptor Compound Classes Uncovers Gαi Protein- and β-Arrestin2-Biased Ligands

Abstract: After the recent description of ␤-arrestin2 recruitment to the human histamine H 4 receptor (hH 4 R) in response to the well known H 4 R antagonist 1-[(5-chloro-1H-indol-2-yl)carbonyl]-4-methyl-piperazine (JNJ 7777120), we evaluated in this study the efficacy of 31 known hH 4 R ligands to induce G␣ i protein signaling and ␤-arrestin2 recruitment by the hH 4 R. The selected hH 4 R ligands belong to nine different structural classes that partly cover (pre)clinical trial candidates. We have identified hH 4 R liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…Very different EC 50 values for partial agonists also have been reported for m-opioid receptors (McPherson et al, 2010;Nickolls et al, 2011), histamine H 4 receptors (Nijmeijer et al, 2012), and b 1 -adrenoceptors (Casella et al, 2011). This suggests that effective bias may be obtained through combinations of efficacies and affinities for the receptor as it interacts with different pathways.…”
Section: Quantifying Biasmentioning
confidence: 99%
“…Very different EC 50 values for partial agonists also have been reported for m-opioid receptors (McPherson et al, 2010;Nickolls et al, 2011), histamine H 4 receptors (Nijmeijer et al, 2012), and b 1 -adrenoceptors (Casella et al, 2011). This suggests that effective bias may be obtained through combinations of efficacies and affinities for the receptor as it interacts with different pathways.…”
Section: Quantifying Biasmentioning
confidence: 99%
“…Of note, differences in functional K A values derived from fitting the operational model may arise from the presence of noninterconverting states that are unique to ligand-receptor-effector complexes (Leff et al, 1997;Holst et al, 2001;Zheng et al, 2008;McPherson et al, 2010;Strachan et al, 2010;Nijmeijer et al, 2012), and this is observed for peptide agonists at the wild-type GLP-1R (Supplemental Table S2). …”
Section: Glp-1r Residues Important For Activity and Modulationmentioning
confidence: 99%
“…The reported biased H 4 receptor signaling by JNJ-7777120 has in the meantime been extended to a broader range of benzimidazole analogs (Nijmeijer et al, 2013), but testing a variety of known H 4 receptor ligands has resulted in the identification of biased ligands for both the G protein and b-arrestin pathways (Nijmeijer et al, 2012).…”
Section: E H 4 Receptor-selective Ligandsmentioning
confidence: 99%